Вирішення Конституційним Судом України публічно-правових спорів про компетенцію (в аспекті національної безпеки) - Потьомкін, А.О. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье рассматриваются вопросы: признания за Конституционным Судом Украины, статуса субъекта обеспечения национальной безопасности Украины; разрешения в ходе конституционного правосудия публично-правовых споров (конфликтов) о компетенции, возникающих между органами государственной власти. The article considers the following issues: recognition of the Constitutional Court of Ukraine as a subject of ensuring national security of Ukraine; settlement of public and legal competence disputes (conflicts) which emerge among state bodies and bodies of local self-government in the course of constitutional justice.